The entrapment of kojic oleate in bilayer vesicles - A. Manosroi (2018)
The entrapment of kojic acid and its newly synthesized ester (kojic oleate) has been evaluated. Kojic oleate was synthesized by DCC (N,N′- dicyclohexylcarbodiimide, DCC)/(4-(N,N-dimethylamino)pyridine, DMAP) esterification method and identified by FAB-MS and1H NMR. The synthesized product was mainly 7-O-kojic oleate with more than 80% yield. It was entrapped in vesicular membrane prepared from 9.5:9.5:1.0 molar ratio of amphiphiles (Span 60, Tween 61 or DPPC), cholesterol and dicetyl phosphate. Kojic acid was encapsulated in the water compartment of these vesicles in order to confirm the vesicle formation. The morphology and particle size of the vesicles were characterized by an optical microscope and transmission electron microscope (TEM). The entrapment efficiencies of kojic acid and kojic oleate in the vesicles were investigated by dialysis and column chromatography, respectively. The contents of the entrapped kojic acid and kojic oleate were assayed by HPLC. The entrapment efficiency of kojic acid was 0.01-0.04 mol, whereas kojic oleate gave higher entrapment efficiency of 0.25-0.35 mol/mol of the total compositions of amphiphile/cholesterol/dicetyl phosphate. Structural modification of kojic acid improved its entrapment in the vesicles. Tween 61 vesicles could entrap kojic oleate more than did Span 60 vesicles. The π-A isotherms revealed the lower area per molecule of Span 60, which formed a more rigid pack of its molecule on air/water interface than that of Tween 61. This implied the high rigidity of vesicular membrane prepared with Span 60 led to the lower amount of kojic oleate entrapped in the vesicles. From the release study of kojic acid through the dialysis membrane, it indicated that the intercalation of kojic oleate in the vesicular membranes did not significantly affect the release of kojic acid from the vesicles. © 2005 Elsevier B.V. All rights reserved.